Insolation and Greenhouse Gas Forcing of the South American Monsoon System Across Three Glacial‐Interglacial Cycles. Issue 14 (23rd July 2020) - Hou, Alicia; Bahr, André; Raddatz, Jacek; Voigt, Silke; Greule, Markus; Albuquerque, Ana Luiza; Chiessi, Cristiano M.; Friedrich, Oliver
Abstract: Precipitation extremes with devastating socioeconomic consequences within the South American Monsoon System (SAMS) are expected to become more frequent in the near future. The complexity in SAMS behavior, however, poses severe challenges for reliable future projections. Thus, robust paleomonsoon records are needed to constrain the high spatiotemporal variability in the response of SAMS rainfall to different climatic drivers. This study uses Ti/Ca ratios from X‐ray fluorescence scanning of a sediment core retrieved off eastern Brazilian to trace precipitation changes over the past 322 Kyr. The results indicate that despite the spatiotemporal complexity of the SAMS, insolation forcing is the primary pacemaker of variations in the monsoonal system. Additional modulation by atmospheric p CO2 suggests that SAMS intensity over eastern Brazil will be suppressed by rising CO2 emissions in the future. Lastly, our record reveals an unprecedented strong and persistent wet period during Marine Isotope Stage 6 driven by anomalously strong trade winds. Key Points: Insolation is the main driver of orbital‐scale South American Monsoon System rainfall variability in eastern Brazil over the past 322 kyr Monsoonal rainfall intensity is indirectly modulated by greenhouse gas forcing through changes to the latitudinal temperature gradients During MIS 6, precipitation in eastern Brazil remained anomalously strong and deviated from the regular orbitally paced insolation forcing